2009
DOI: 10.1007/s00436-009-1441-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficacy of tetracycline by acaciasides on Dirofilaria immitis

Abstract: The discovery of Wolbachia, a bacterial endosymbiont that occurs in the filarial parasite and its sensitivity to tetracycline, has fostered a new initiative in the development of suitable antifilarial drugs. The present study is an attempt to investigate whether adding acaciasides (saponins from Acacia auriculiformis) to the standard dose of tetracycline would further improve the efficacy of tetracycline treatment against Dirofilaria immitis microfilariae in vivo. Treatment of microfilaremic adult dogs (body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In BALB/c mice infected with Litomosoides sigmodontis and treated with rifampin alone or with doxycycline for 14 days, the elimination of Wolbachia from worms and the inhibition of development and embryogenesis were shown, and few worms survived after treatment (446). Microfilaricide and adulticide activity (163) and the total elimination of microfilariae for at least 4 months were found when tetracycline treatment was followed by the administration of acaciasides (Acacia auriculiformis-derived saponins) (104). The effects of antibiotic treatment on D. immitis-infected dogs have also been studied.…”
Section: Wolbachia As a Therapeutic Targetmentioning
confidence: 99%
“…In BALB/c mice infected with Litomosoides sigmodontis and treated with rifampin alone or with doxycycline for 14 days, the elimination of Wolbachia from worms and the inhibition of development and embryogenesis were shown, and few worms survived after treatment (446). Microfilaricide and adulticide activity (163) and the total elimination of microfilariae for at least 4 months were found when tetracycline treatment was followed by the administration of acaciasides (Acacia auriculiformis-derived saponins) (104). The effects of antibiotic treatment on D. immitis-infected dogs have also been studied.…”
Section: Wolbachia As a Therapeutic Targetmentioning
confidence: 99%
“…Saponins form complexes with sterols and cause sterol-dependent membrane permeabilization. The antimicrobial activity of saponins is generally attributed to these membranepermeabilizing properties (Datta et al, 2009;Yang et al, 2006). Studies have demonstrated that membrane impermeability plays an important role in resistance to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which such a combination achieves synergy is believed to be by facilitating the entry of the antimicrobial compounds into cells after the partial disruption of the cell membrane through its action. Moreover, it is possible that the positive interaction is a result of a combined effect of increased access to the intracellular target for vancomycin or daptomycin and the secondary effects of the saponins themselves (Datta et al, 2009;Sung & Lee, 2008).…”
Section: Discussionmentioning
confidence: 99%